The educational potential of the theory of social representations applied to climate change: A critical literature review - Harumi Takano Rojas; Alicia Castillo; Pablo Meira-Cartea (Revista Española de Pedagogía)
Social representation theory provides a theoretical framework for comprehending how information about climate change is transformed as it moves from the scientific realm and becomes intertwined with people’s everyday lives. It also explores the relationship between this knowledge and the shared values, beliefs, and ideas within a specific social group. This article critically reviews 67 papers on social representations of climate change, identifying main contributions, methodological approaches, and future research opportunities. This review offers a broad outlook on the knowledge provided by social representation theory to understand climate change from a social-educational perspective.